The relationship of ERG potassium channel with programmed cell death in the vertebrate developing limb - Félix, Rita Leiria Lopes, 1987- (2011)
Tese de mestrado. Biologia (Biologia Evolutiva e do Desenvolvimento). Universidade de Lisboa, Faculdade de Ciências, 2010